Ethnobotanical Review and Potential Diversity of Zingiberaceae Species as Postpartum Medicinal Ingredients in the Interior of Kalimantan - Letus Sepsamli; Septaria Yolan Kalalinggi; Reza Raihandhany; Syamswisna; Widia Sri Utami (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2025)
The local communities in the interior of Kalimantan have long utilized plants from the Zingiberaceae family as traditional medicinal ingredients, especially for postpartum care. Many species of Zingiberaceae are retained in postnatal care because they are effective in alleviating and healing ailments. This study aims to review the potential diversity of Zingiberaceae species used in traditional medicine after childbirth and to identify their chemical compound content. The method used is a literature review with an analysis of scientific literature from the past 10 years discussing the utilization of Zingiberaceae by the community in Kalimantan in managing mothers after childbirth. The results show that there are ten species and four genera of Zingiberaceae that are frequently used, namely Alpinia, Kaempferia, Curcuma, and Zingiber. The plant organ that is utilized is the rhizome, processed in various ways such as boiling, pounding, or turning into powder before being consumed or applied to the body. The compound content in Zingiberaceae includes curcumin, gingerol, and shogaol, which have immunomodulatory, anti-inflammatory, and antioxidant activities, playing a role in postpartum treatment for women. This research emphasizes that Zingiberaceae plays an important role in traditional postnatal treatment, and further studies are needed to support the preservation of local knowledge, as well as conservation and sustainable utilization.